Analisis Manajemen Risiko Keuangan Pada UMKM Tegar Bakery Karawang - Rachman, Cinta Chantika Suryana; Isyanto, Puji (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Risk management is carried out to manage all possible risks that arise. Apart from that, financial risks also have a significant influence on MSME players. The purpose of this research is to determine the financial risks that may be faced by UMKM Tegar Bakery. The research was conducted using a qualitative analysis approach. The results show that financial management has a significant influence on MSMEs. This shows that the ability to manage finances well can improve the performance and sustainability of MSME businesses.